2019
DOI: 10.1002/pola.29540
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of 9,9‐bis(4‐hydroxyphenyl and 4‐aminophenyl)dibenzofluorenes: Novel fluorene‐based monomers

Abstract: Two novel 9,9‐difunctionalized fluorene‐type monomers, 9,9‐bis(4‐hydroxyphenyl‐ and 4‐aminophenyl)‐2,3:6,7‐dibenzofluorenes, are synthesized by the reaction of dibenzenzofluorenone with phenol and aniline. These monomers are used for the preparation of polyester and polyimide as the typical polymers to evaluate the property change such as thermal stability caused by the benzene rings fused to the fluorene skeleton with keeping good solubility, in comparison with the polymers derived from simple fluorenone. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It has been shown to improve the solubility and thermal stability of polyarylate compounds by modifying the structure of the molecular chain. [17][18][19][20] Yogeshwar K. Chamkure et al reported a new polyarylate containing a BHPF pendant unit synthesized from 2-acetylfluorene and phenol, which showed high thermal stability and solubility. 21 The random introduction of the BHPF structure into the molecular chain of semi-crystalline BPA-based polyarylate was expected to lead to polyarylate with desirable comprehensive performance by adjusting the ratio of structural units as well as adjusting the structure of the polymer molecular chain.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to improve the solubility and thermal stability of polyarylate compounds by modifying the structure of the molecular chain. [17][18][19][20] Yogeshwar K. Chamkure et al reported a new polyarylate containing a BHPF pendant unit synthesized from 2-acetylfluorene and phenol, which showed high thermal stability and solubility. 21 The random introduction of the BHPF structure into the molecular chain of semi-crystalline BPA-based polyarylate was expected to lead to polyarylate with desirable comprehensive performance by adjusting the ratio of structural units as well as adjusting the structure of the polymer molecular chain.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1920s, polyesters have been extensively studied, and still, current research deals with enhancing kinetic models, introducing innovative monomers, finding new applications, or applying special analytical techniques. This interest can be explained by the great versatility of this polymer group arising from numerous suitable monomers. Apart from necessary carboxyl and hydroxyl moieties for esterification, monomers often carry additional functional groups.…”
mentioning
confidence: 99%